Self-Regulated Learning Through The Ethno-Flipped Classroom Model: A Study of Stacking Analysis in Rasch Measurement - Rahmi Ramadhani; Siti Aisyah; Haryati Ahda Nasution (Jurnal Pendidikan Terapan, 2026)
Purpose: This study aims to evaluate the effectiveness of the ethno-flipped classroom model, which integrates Nias cultural artifacts, in enhancing students’ self-regulated learning (SRL) in statistics. Methods: This study employed a quantitative approach with a longitudinal design. Data were collected from 152 students at the Senior High School residing on Nias Island, Indonesia via SRL questionnaires administered at the pre- and post-intervention stages. Data analysis utilized stacking analysis within the Rasch Model framework to measure growth in ability on a consistent logit scale, supplemented by in-depth interviews to clarify inconsistent response patterns. Findings: The results showed a significant increase in students’ self-regulated learning, with the percentage of students at the “High” level surging dramatically from 17.76% at the pre intervention stage to 76.35% at the post-intervention stage. All students demonstrated positive logit score growth, reflecting a paradigm shift in learning from individualistic to collaborative approaches. However, it was found that students with low initial mathematics ability still require additional support during the self-monitoring phase. Research Implications: These findings provide practical contributions for educators in designing instructional approaches that integrate modern technology with local wisdom to strengthen student autonomy and engagement. However, this study is limited by students' adaptation difficulties, self-monitoring gaps among low and moderate ability students, and the Nias cultural context restricting generalizability. Originality: The novelty of this research lies in the unique integration of Nias-specific ethno-mathematics artifacts into a flipped classroom model, validated using the psychometric Rasch Model approach to ensure the objectivity of student ability growth measurements.